1981
DOI: 10.1136/thx.36.2.116
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between asthma and gastro-oesophageal reflux.

Abstract: Twenty patients with bronchial asthma who also had gastro-oesophageal reflux were investigated. The severity of their reflux was graded using symptom score of heartburn and regurgitation and by the following investigations: barium swallow and meal, fibreoptic endoscopy and biopsy, manometry and pH monitoring of the distal oesophagus, and an acid infusion test. Full lung function studies were performed and patients were entered into a double-blind crossover study using cimetidine to control their reflux in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0
3

Year Published

1985
1985
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(57 citation statements)
references
References 19 publications
0
54
0
3
Order By: Relevance
“…Representative data from a control subject and the asthmatic patients are shown in figs 2 Time (hours) Figure 3 Data from four patients complaining of nocturnal asthma presented as in fig. 2.…”
Section: Resultsmentioning
confidence: 99%
“…Representative data from a control subject and the asthmatic patients are shown in figs 2 Time (hours) Figure 3 Data from four patients complaining of nocturnal asthma presented as in fig. 2.…”
Section: Resultsmentioning
confidence: 99%
“…There have been many studies dealing with asthma outcome and medical anti-reflux therapy. Field and Sutherland (1998) reviewed the previously published data on medical anti-reflux therapy with H 2 -receptor blockers (H 2 blockers), cimetidine (Goodall et al 1981;Larrain et al 1991) and ranitidine (Harper et al 1987;Nagel et al 1988;Ekstrom et al 1989;Gustaffson et al 1992), and with a proton pump inhibitor (PPI) omeprazole (Ford et al 1994;Meier et al 1994;Harding et al 1996;Teichtahl et al 1996), showing that asthma symptoms were improved. Kiljander (2003) suggested that, in the management of GERD-related asthma, PPIs other than omeprazole should be used at double the standard dose.…”
mentioning
confidence: 99%
“…Field et al (13) found that 41% experienced RARS and 28% used their rescue beta agonist during episodes of symptomatic GER. Goodall et al (33) reported a correlation between the severity of GER and asthma symptoms. Harding et al (34) reported a temporal correlation between GER, documented by ambulatory pH monitoring, and respiratory symptoms in asthma patients.…”
Section: Do Bronchodilators Cause Ger?mentioning
confidence: 99%
“…A recent critical review identified 12 English-language studies of the effects of medical antireflux therapy in people with asthma with GER (76). In the eight controlled studies, two used cimetidine, four ranitidine and two omeprazole (10,32,33,(67)(68)(69)77,78). A critical review of the controlled studies indicates that medical antireflux therapy improved GER symptoms, asthma symptoms and asthma medication requirements (76).…”
Section: Effects Of Medical Antirefluxmentioning
confidence: 99%
See 1 more Smart Citation